RETRACTED: Strategy of increasing protein production based on lupin and nano disintegrator technology - Ivanov Igor; Persiyanova Galina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001